2010
DOI: 10.1186/0778-7367-68-1-30
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead levels in the Kinshasa population: a pilot study

Abstract: ObjectiveLeaded gasoline and lead paints are still in use in the Democratic Republic of Congo but data on blood lead levels in the general population are not available. We evaluated the Pb impregnation in children and adults (0 - 70 years old) in Kinshasa.MethodsBlood lead was measured by atomic absorption in a sample of 485 healthy people (268 men and 217 women) living in Kinshasa between May 2003 and June 2004.ResultsGeometric mean blood lead was 120 µg/L (95% CI: 115-125), with a higher concentration in men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
13
2
Order By: Relevance
“…Demographic characteristics (age and sex) of children in this study were compared to those found in the same population in 2004 and 2008 [15,16]. No significant differences were observed between the subgroup studied (Table 1), indicating that our sampling strategy (unweighted clusters) did probably not introduce a strong bias in the representativeness of our population sample.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Demographic characteristics (age and sex) of children in this study were compared to those found in the same population in 2004 and 2008 [15,16]. No significant differences were observed between the subgroup studied (Table 1), indicating that our sampling strategy (unweighted clusters) did probably not introduce a strong bias in the representativeness of our population sample.…”
Section: Discussionmentioning
confidence: 83%
“…The prevalence of elevated BLLs in current study (41%) decreased dramatically as it was in 2004 (63%) and 2008 (71%), probably because of the DRC has recently completed in 2009 the phase out of lead in gasoline: a 30% decrease 2 years after the phase out of lead in gasoline began compared with studies the same population before the phase out [15,16]. Predictable reductions in BLLs have been described in several countries [12,13].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations